Про вплив на екологічну ефективність централізованих систем теплопостачання - Елькін, Юрій Генрихович; Воінов, Олександр Петрович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Централізовані системи теплопостачання як складні та відповідальні елементи енергетики є екологічно вельми агресивними. Метою роботи є аналіз стану їх взаємодії з природним середовищем та пошук шляхів вирішення її протиріч. Діючі централізовані системи теплопостачання є низькоефективними, через високий знос їх елементів, особливо котельних установок. Одним із шляхів підвищення їх ефективності, в тому числі екологічності, може бути часткове оновлення. Часткове оновлення всього обладнання вказаних систем дозволяє підвищити рівень його екологічності в цілому.

The global production created by the mankind has an intensively increasing harmful effect on the environment. As a result, we are facing the problem of the saving of natural environment and now the global community tries to find solution for this environmental problem. The power generation sector is the most environmentally aggressive of all industry branches. Technical power engineering facilities differ by a high degree of complexity making it difficult to increase the level of their environmental friendliness. In particular, centralized heat supply systems are rather complicated and responsible components of the power engineering industry. These differ by a high level of environmental aggressiveness. Hence, these need to increase a degree of their environmental friendliness. The purpose of this research was to analyze the condition of the interaction of the power generating sector with the natural environment and search for harmonization solutions of available contradictions of such an interaction. An increase of the environmental friendliness of the worn-out power equipment used by centralized heat supply systems is a topical problem. The purpose of this scientific paper was to suggest a solution for the problem of the environmental interaction of the centralized heat supply systems with natural environment using an approach of their partial renewal. The most environmentally aggressive elements of these systems are the boiler plants that emit heat and harmful substances into the environment.
About the effect on the environmental efficiency of the centralized heat supply systems
Keywords: централізована система теплопостачання; котельна установка; екологічність; часткове оновлення; centralized heat-supply system; boiler plant; environmental friendliness; partial renewal